High-stress three-body abrasive wear of treated and untreated oil palm fibre-reinforced polyester composites - El-Tayeb, N S M; Yousif, B F (PROFESSIONAL ENGINEERING PUBLISHING LTD, 2008)
The aim of this study is to investigate the effect of treated and untreated oil palm fibres on high-stress three-body abrasive wear characteristics of polyester composites. Experimental tests were conducted at different applied loads (5-20 N) and two different rotational speeds (50 and 100r/min) for 0.18km sliding distance using a dry sand/steel wheel apparatus. The flow of the sand particles (560-900 mu m) was 4.5g/s. Morphologies of the worn surface of the composites were studied using a scanning electron microscope (SEM). Pull-out test was carried out to evaluate the interfacial adhesion characteristics of treated and untreated fibres. The results revealed that composites based on treated oil palm fibres exhibited better wear performance compared with untreated ones, i.e. the interfacial adhesion of treated fibres to the polyester was better than untreated fibres. Moreover, treated oil palm fibres were found to reduce the porosity of the composite, which in turn stabilized the surface tribo-characteristics. Based on the SEM analysis, the wear mechanisms were predominated by pitting, grooving, microcracking, microcutting, and fracture in the polyester region.